Aplikasi Game Edukasi Tarian Daerah dan Rumah Adat Daerah Berbasis Android - Rindyana, Elva Yundra (Universitas Trilogi, 2019)
The purpose of the research is as a medium for learning traditional dances and regional traditional houses and can be used as a debriefing for the community to better know the traditional dances and regional traditional houses properly. The research method used is the System Development Life Cycle (SDLC) waterfall method, a research method that has the characteristics of each phase in the waterfall must be completed before proceeding to the next phase The analytical aid used is Flowchart and Unified Modeling Language. Software used with the help of the Java programming language, Android Studio Editor, Android Standard Development Kit, and Android Development Tools. The conclusion is that this application was built so that it can provide convenience in learning regional dance education and local traditional houses.